2014
DOI: 10.1590/s1516-35982014000300008
|View full text |Cite
|
Sign up to set email alerts
|

Performance and carcass traits of Moxotó growing goats supplemented on native pasture under semiarid conditions

Abstract: -The objective of the present study was to assess the growth performance and carcass traits of Moxotó goat kids fed different levels concentrate (supplement) (SL) on native pasture under semiarid conditions in Brazil. Thirty-two castrated kids (15.7±0.78 kg initial BW) were allocated randomly to one of the four SL (treatment groups: 0, 5, 10 and 15 g/kg BW). When the animals of treatment group 15 g/kg BW reached 25 kg BW, the animals in the other treatments groups were also slaughtered. Therefore, the animals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 28 publications
2
3
0
4
Order By: Relevance
“…The empty weight (7.75-11.35kg) obtained in this study is lower than 13.09-19.72kg reported by Marques et al (2014) for Moxotó growing goats, but somehow comparable with 8.1-9.2kg reported by Grum (2010) for Kano brown goats. The warm carcass weight (4.43-7.17kg) obtained in this study is lower than 11.01kg reported by Rodriguez et al (2014) and higher than 3.40-4.65kg reported by Ifut et al (2011).…”
Section: Discussionsupporting
confidence: 80%
“…The empty weight (7.75-11.35kg) obtained in this study is lower than 13.09-19.72kg reported by Marques et al (2014) for Moxotó growing goats, but somehow comparable with 8.1-9.2kg reported by Grum (2010) for Kano brown goats. The warm carcass weight (4.43-7.17kg) obtained in this study is lower than 11.01kg reported by Rodriguez et al (2014) and higher than 3.40-4.65kg reported by Ifut et al (2011).…”
Section: Discussionsupporting
confidence: 80%
“…The fact that only the shoulder exhibited differentiated growth is due to the greater amount of bones it contains; thus, the proportion will be greater in leaner carcasses. MARQUES et al (2014) studied increasing levels of concentrate supplementation (0, 5, 10 and 15g kg -1 of BW) in Moxotó goats (with similar BW to our study) grazing in the semiarid region and observed that the weights of the neck, rib, shoulder and leg cuts also increased. The proportion of the shoulder was the only cut influenced by the feed restriction levels, as observed in the present study.…”
Section: Variablessupporting
confidence: 64%
“…A menor deposição de gordura em animais submetidos à restrição pode ser explicada pelo menor consumo de energia, haja vista que a exigência energética para a lipogênese é elevada. Em outros estudos também foi verificada menor deposição de lipídeos em função da redução na ingestão de energia (BEZERRA et al, 2010;LISBOA et al, 2010;MARQUES et al, 2014). Mesmo em condição de restrição alimentar, os caprinos Canindé apresentaram deposição de gordura total no corpo superior à deposição em caprinos castrados da raça Saanen com pesos semelhantes (FIGUEIREDO, 2014), o que pode demonstrar a reserva energética como prioridade para as raças nativas e naturalizadas.…”
Section: Resultsunclassified